Practical Evaluation and Complexity Analysis of Forgery Attacks on the PAES-8 Authenticated Encryption Scheme - Windarta, Susila; Purbasari, Imas (Buletin Pos dan Telekomunikasi, 2024)
The Parallelizable Authenticated Encryption Scheme (PAES)-8, designed by Ye et al. in 2014, claims to provide 128-bit authentication security in the nonce-misuse model. However, Sasaki and Wang's theoretical forgery attack on PAES-8 exposed vulnerabilities, suggesting a universal forgery with a complexity of approximately . This study presents a practical implementation of Sasaki and Wang’s theoretical forgery attack on the PAES-8 encryption scheme, uncovering significant modifications required for its execution. This including the use of DDT-based plaintext injection, staged state recovery, multiple injection attempts, and algorithmic adjustments. Our findings demonstrate that these modifications increase the attack complexity to approximately 211+212+27 = 212, indicating greater resistance in PAES-8 than previously anticipated. Future cryptanalysis should focus on exploring nonce-respecting models to evaluate the scheme’s security.